Potensi Budidaya Limnocharis Flava L dalam Peningkatan Pendapatan Ekonomi Masyarakat di Aceh Tenggara - Assauwab, Muhammad Husaini; Yusuf, Husainah; Abdi, Zeni; Munthe, Muhammad Nur (JURNAL AGROPLASMA, 2023)
Limnocharis flava L., is a plant native to Latin America and tropical regions that has been introduced to South and East Asia. This plant is a potential source of nutrition as it contains various nutrients, including protein, fat, carbohydrates, vitamins, minerals, fiber, and antioxidants. It is commonly consumed as a vegetable, and its leaves and flowers have a high economic value and are sold in traditional and modern markets. The cultivation of genjer has promising potential, as observed in some areas of Indonesia where it can be grown on a large scale with good profitability. Therefore, a study was conducted on the potential cultivation of Limnocharis flava L in improving the economic income of communities in Southeast Aceh. The research used an exploratory method, including surveys, observations, and questionnaire results in Southeast Aceh district. Although genjer is still not widely cultivated, observations in several areas in Indonesia have shown that the plant can be grown on a large scale with good profitability. Genjer farmers in Southeast Aceh have an average income of Rp.619,632 per month.Â Keywords: Economic, Genjer, Food, simple, Traditional.